Regulation of apoptosis through bcl-2/bax proteins expression and DNA damage by nano-sized gadolinium oxide - Alarifi S (Dove Medical Press, 2017)
Saud Alarifi,1 Huma Ali,2 Saad Alkahtani,1 Mohammed S Alessia3 1Department of Zoology, College of Science, King Saud University, Riyadh, Saudi Arabia; 2Department of Chemistry, Maulana Azad National Institute of Technology Bhopal, MP, India; 3Department of Biology, Faculty of Science, Al-Imam Muhammad Ibn Saud Islamic University, Riyadh, Saudi Arabia Abstract: Gadolinium oxide (Gd2O3) nanoparticles (GNPs) are applied in industrial products, for example, additives, optical glass, and catalysis. There are various suggestions of metal nanoparticles paradigm but the underlying basic mechanism about the toxicity of metal nanoparticles, for example GNPs, remains unclear. This experiment was done to measure the effective toxicity of GNPs (10, 25, 50, and 100 µg/mL) over 24 and 48 h and to evaluate toxicity mechanism in human neuronal (SH-SY5Y) cells. GNPs produced reactive oxygen species (ROS), as evaluated by 2', 7'-dichlorodihydrofluorescein diacetate. Due to incorporation into cells, GNPs generated ROS in a concentration- and time-dependent manner. To determine the toxicity of GNP mechanism related to ROS, we also found chromosome condensation and dysfunction of mitochondrial membrane potential (MMP) after exposure of GNPs. Furthermore, the increased cell apoptosis rate and DNA fragmentation were closely related to the increased dose and exposure duration of GNPs in SH-SY5Y cells. The reduction in MMP with a simultaneous increase in the expression of bax/bcl2 gene ratio indicated that mitochondria-mediated pathway involved in GNPs induced apoptosis. Thus, our finding has provided valuable insights into the probable mechanism of apoptosis caused by GNPs at in vitro level. Keywords: GNPs, SH-SY5Y cells, apoptosis, ROS, DNA fragmentation